The relationship between macroeconomic variables, exchange rate and stock price: Malaysian evidence / Faridah Najuna Misman and Intan Safura Jilani - Misman, Faridah Najuna; Jilani, Intan Safura (2008)
Macroeconomic variables and exchange rate are among the most important indicators to the stock price changes and to the stock market performance. It is important to know the relationship between the macroeconomic variables, exchange rate and the stock price in order to help investors to make a right decision accordingly. Thus, this study aims to analyze the relationship between the macroeconomic variables, exchange rate and stock price in Malaysia for the period of January I997 to December 2006. In this study, the macroeconomic variables are: money supply (M2), inflation, interest rate and exchange rate. As a proxy to the stock price, the Kuala Lumpur Composite Index and several other Sector Indices will be used in the analysis. A multiple linear regression will be applied in this study to analyze the relationship between the dependent and independent variables. This study indicates that, the Malaysian stock price seems to be driven more by the changes in the domestic sectors such as a money supply and exchange rate.